Histamine : a potential cytoprotective agent to improve cancer therapy? - Martinel Lamas, Diego J. (2015)
Fil: Martinel Lamas, Diego J. Universidad de Buenos Aires. Facultad de Farmacia y Bioquímica; Argentina